2011
DOI: 10.1111/j.1349-7006.2011.02100.x
|View full text |Cite
|
Sign up to set email alerts
|

Insulin‐like growth factor II mRNA‐binding protein 3 expression predicts unfavorable prognosis in patients with neuroblastoma

Abstract: Insulin-like growth factor II mRNA-binding protein 3 (IMP3) has been reported to enhance proliferation and invasion in various cancers. The role of IMP3 on neuroblastoma (NB) is unknown. We aimed to clarify the prognostic significance of IMP3 expression in patients with NB. By microarray analysis, high IMP3 expression was found in patients with poor outcome. IMP3 expression in 90 NB samples was analyzed by immunohistochemical staining to correlate with clinical stages, histology, and patient outcome. Positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…The 53 studies involved 8,937 patients with different cancer types, including 6 studies of RCC,8,2529 6 lung cancer,9,30–34 4 oral cancer,10,3537 4 urothelial carcinoma,3841 4 ovarian cancer,16,17,42,43 3 hepatocellular carcinoma (HCC),4446 4 colorectal cancer,12,4749 3 prostate cancer,14,15,50 3 pancreatic cancer,5153 2 gastric cancer,11,54 2 intrahepatic cholangiocarcinoma (ICC),55,56 and one study each of tongue cancer,57 thyroid carcinoma,58 sacral chordoma,59 pilocytic astrocytoma and pilomyxoid astrocytoma (PA/PMA),60 neuroblastoma,61 meningioma,62 melanoma,63 breast cancer,64 giant cell tumor,65 bile duct carcinoma,66 esophageal carcinoma,67 and cervical cancer 13. A total of 25 studies involved Caucasians and 28 involved Asians.…”
Section: Resultsmentioning
confidence: 99%
“…The 53 studies involved 8,937 patients with different cancer types, including 6 studies of RCC,8,2529 6 lung cancer,9,30–34 4 oral cancer,10,3537 4 urothelial carcinoma,3841 4 ovarian cancer,16,17,42,43 3 hepatocellular carcinoma (HCC),4446 4 colorectal cancer,12,4749 3 prostate cancer,14,15,50 3 pancreatic cancer,5153 2 gastric cancer,11,54 2 intrahepatic cholangiocarcinoma (ICC),55,56 and one study each of tongue cancer,57 thyroid carcinoma,58 sacral chordoma,59 pilocytic astrocytoma and pilomyxoid astrocytoma (PA/PMA),60 neuroblastoma,61 meningioma,62 melanoma,63 breast cancer,64 giant cell tumor,65 bile duct carcinoma,66 esophageal carcinoma,67 and cervical cancer 13. A total of 25 studies involved Caucasians and 28 involved Asians.…”
Section: Resultsmentioning
confidence: 99%
“…10,25 Specifically, increased protein expression of IGF2BP3 has been associated with enhanced tumor aggressiveness, metastatic behavior and inferior outcome of various solid cancers. [12][13][14][15][16][17][18] Recently, there has been growing interest in the IGF pathway from a therapeutic perspective, as monoclonal antibodies and small molecules targeting the IGF1 receptor have become available a few years ago and initial, small phase I and II, trials showed encouraging results in individual patients. 25 In this study, we investigated the mRNA expression levels of several molecules involved in IFG signaling in mantle cell lymphoma cell lines and primary mantle cell lymphoma cases.…”
Section: Discussionmentioning
confidence: 99%
“…11 More recently, increased IGF2BP3 protein expression has been reported in a variety of solid tumors and was found to be associated with a higher histological grade, 12 progression or metastasis 13,14 and with an unfavorable outcome. [15][16][17][18] These data indicate that IGF2BP3 may promote tumor cell proliferation and progression by enhancing signaling via the IGF pathway. In lymphoid cells, IGF2BP3 is physiologically expressed in normal germinal center B cells and an initial study described variable IGF2BP3 protein expression in different types of malignant lymphomas, particularly in those with an association to a germinal center B-cell phenotype.…”
mentioning
confidence: 86%
“…Periosteal osteosarcoma, is an intermediate grade chondroblastic osteosarcoma arising on the surface of bone periosteal osteosarcoma is associated with a better prognosis than conventional osteosarcoma (Fletcher et al 2002). The invasion ability of neuroblastoma cells decreased as IMP3 knock-down by using RNA interference in vitro, and high expression of IMP3 in neuroblastoma may contribute to the undifferentiated phenotype and invasive behaviors, leading to a poor prognosis (Chen et al 2011). In the present study, the parosteal and periosteal osteosarcoma have better prognosis than the conventional osteosarcoma, but the reasons remains unknown except for the histological differentiation (Fletcher et al 2002).…”
Section: Introductionmentioning
confidence: 98%